Evaluation of inhibitive corrosion potential of symmetrical hydrazine derivatives containing nitrophenyl moiety in 1M HCl for C38 steel: experimental and theoretical studies. Issue 3 (March 2022) - Lakbaibi, Zouhair; Damej, Mohamed; Molhi, Abdu; Benmessaoud, Mohammed; Tighadouini, Said; Jaafar, Adil; Benabbouha, Tariq; Ansari, Abdeselam; Driouich, Anas; Tabyaoui, Mohamed
Abstract: The exploitation of cost-effective, sustainable, green and efficient compounds is a renewed science and a demanding mission for today's chemists and technologists. In this view, the inhibitive corrosion properties of some hydrazine derivatives named (1 E, 2 E )-bis(1-(2-nitrophenyl)ethylidene)hydrazine (SSBO ), (1 E, 2 E )-bis(1-(3-nitrophenyl)ethylidene)hydrazine (SSBM ) and (1 E, 2 E )-bis(1-(4-nitrophenyl)ethylidene)hydrazine (SSBP ) on the C38 steel corrosion in 1M HCl media has been evaluated by different techniques like electrochemical impedance spectroscopy (EIS), potentiodynamic polarization (PDP), scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy. The EIS results showed that SSBM is the greatest inhibitor ( η > 93 %) among the three tested compounds. The SSBM gives considerable inhibition efficiency against corrosion of steel compared to the previous studies. The PDP curves indicated that the studied inhibitors were a mixed-type inhibitor with a predominantly cathodic control. Quantum calculations of some descriptors derived from the density functional theory (DFT), the transition state theory (TST), the quantum theory of atoms in molecules (QTAIM) and molecular dynamics simulation have delivered helpful information regarding electron transfer and mechanism during adsorption of inhibitors on C38 steel surface. Abstract : Hydrazine derivatives; Nitrophenyl; Green; C38 steel corrosion; DFT; QTAIM; Molecular dynamics simulation